Results from the China 2022 report card on physical activity for children and adolescents - Yang Liu; Youzhi Ke; Yahan Liang; Zheng Zhu; Zhenbo Cao; Jie Zhuang; Yujun Cai; Lijuan Wang; Peijie Chen; Yan Tang (Journal of Exercise Science & Fitness, 2023)
Background/Objective: Regular physical activity (PA) is beneficial to young people's health and development. In order to provide nationally representative and internationally comparable evidence on youth PA, China has participated in Global Matrix 2.0 and 3.0. The purpose of this study is to report the updated results of China's Report Card on PA for Children and Adolescents. Methods: The grades were assigned by results derived from the PA and Fitness in China––The Youth Study (PAFCTYS), conducted from October to December in 2020. The data from PAFCTYS 2020 included a nationally representative sample of Chinese school-aged children (n = 133,006, boys: 49.6%, aged 9–17 years). Self-report questionnaires were completed by the sampled students, their parents/guardians (n = 133,006), and physical education teachers (n = 1036) from each sampled school respectively. Results: The grades of China 2022 Report Card are Overall PA (C), Organized Sport Participation (F), Active Play (C-), Active Transportation (C), Sedentary behaviors (C), Physical Fitness (INC), Family and Peers (C-), School (D), Community and Environment (D-), and Government (D). Conclusion: Levels of PA among Chinese youth were low and most young people were below the recommended guidelines, although the grade of Overall PA has been improved since the modified benchmark. Prevalence of sedentary behaviors remained high. Interventions and policies at the community and environment level should be encouraged to promote PA and reduce sedentary behaviors. In addition, national policies on young people's PA should be advocated widely to ensure the policies can be transferred into action.